Role of gut microflora and probiotic effects in the irritable bowelsyndrome - Fanigliulo, L.; Comparato, G.; Aragona, et al., G. (Acta Biomedica Atenei Parmensis, 2006)
Background. Even though the cause of irritable bowel sindrome (IBS) is not yet known, alterations of the intestinal microflora may be important in its pathogenesis. Aim. To evaluate the efficacy of rifaximine alone or in association with the probiotic strain of Bifidobacterium longum W11 in reducing symptoms in patients with IBS. Methods. We performed a monocentric, prospective, randomized open trial including 70 patients randomized in to two groups: Group A (41 patients) receiving rifaximin 200 (2 cp bid for ten days  in a month) followed by a formulation of the probiotic strain of Bifidobacterium longum W11(one granulated suspension for 6 days on alternate weeks ) and Group B (29 patients) receiving only rifaximin 200 (2 cp bid for ten days in a month). The clinical evaluation was performed at admission and after 2-months, taking into account the method of visual analogous. Results. At the 2-month follow-up, Group A patients reported a greater improvement of symptoms compared to patients in group B (p = 0.010) even if the physician’s opinion at T1 did not confirm these results (p = 0.07). Conclusion. The increased colonisation by Bifidobacterium longum W11, after the cyclic administration of rifaximin, which eradicates the bacterial overgrowth of the small intestine, may reduce symptoms, especially those related to bowel habit and stool frequency in patients with IBS. The abnormalities observed in the colonic flora of IBS suggest, in fact, that a probiotic approach will ultimately be justified.